Analysis of Village Fund Management in Improving the Community Economy in Indonesia - Ningsih, Ratna Nurya; Zaidi, Nurul Ain Binti (SMART Insight, 2024)
This research aims to analyze the management of village funds and its impact on the economy of village communities. Village funds are an allocation of funds from the central government aimed at accelerating village development and improving the welfare of village communities. The research method used is a qualitative method with a case study approach in several villages in various regions in Indonesia. Data was collected through in-depth interviews, field observations, and document analysis. The research results show that effective village fund management can improve infrastructure, expand employment opportunities, and support micro, small and medium enterprises (MSMEs) at the village level. However, this research also identified several obstacles, such as lack of transparency, inadequate management capacity, and low community participation. To optimize the use of village funds, it is recommended to increase the capacity of village officials, tighter supervision, and increase community participation in the planning and monitoring process. In this way, village funds can function optimally in improving the economy and welfare of village communities.